Triple and quintuple hops: Utility, reliability, asymmetry, and relationship to performance - Stolberg, M.; Sharp, A.; Comtois, A.; Lloyd, R. S.; Oliver, J. L.; Cronin, J. (Strength and Conditioning Journal, 2016)
Triple and quintuple hops (THT and QHT, respectively) are used to test repeated propulsion. This narrative review provides information regarding the use of tht and qht, as well as their reliability, testing norms by sex and athletic level, their ability in detecting asymmetry and relevance to other performance measures. The tests' reliability (intraclass correlation coefficient [icc]THT = 0.80-0.98; standard error of the mean [sem]tht = 0.11-0.23 m; iccQHT = 0.89) warrants their inclusion during testing batteries. Tht ranges from 4.28 to 6.90 m and asymmetries range from 10 to 15%. Tht is likely related to acceleration capabilities. Practical recommendations are provided to practitioners regarding tests' administration.